2017
DOI: 10.1038/srep43471
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of atypical MAP kinases ERK3 and ERK4 by the phosphatase DUSP2

Abstract: The atypical MAP kinases ERK3 and ERK4 are activated by phosphorylation of a serine residue lying within the activation loop signature sequence S-E-G. However, the regulation of ERK3 and ERK4 phosphorylation and activity is poorly understood. Here we report that the inducible nuclear dual-specificity MAP kinase phosphatase (MKP) DUSP2, a known regulator of the ERK and p38 MAPKs, is unique amongst the MKP family in being able to bind to both ERK3 and ERK4. This interaction is mediated by a conserved common dock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Analogous to classical MAP kinases, ERK3 is activated by phosphorylation of the activation loop, which stimulates its intrinsic catalytic activity and affinity for the substrate MK5 (7). Activation loop phosphorylation is mediated by Group I p21-activated kinases (8, 9), and is reversed by the action of the MAP kinase phosphatase DUSP2 (10). Of note, it has been previously proposed that ERK3 enzymatic activity is dispensable for MK5 activation and that ERK3 may exert a scaffolding function (11).…”
Section: Introductionmentioning
confidence: 99%
“…Analogous to classical MAP kinases, ERK3 is activated by phosphorylation of the activation loop, which stimulates its intrinsic catalytic activity and affinity for the substrate MK5 (7). Activation loop phosphorylation is mediated by Group I p21-activated kinases (8, 9), and is reversed by the action of the MAP kinase phosphatase DUSP2 (10). Of note, it has been previously proposed that ERK3 enzymatic activity is dispensable for MK5 activation and that ERK3 may exert a scaffolding function (11).…”
Section: Introductionmentioning
confidence: 99%
“…DUSP2 (9). Of note, it has been previously proposed that ERK3 enzymatic activity is dispensable for MK5 activation and that ERK3 exerts a scaffolding function (10).…”
mentioning
confidence: 99%
“…Consistent with this nding, we also noticed that, in present study, the level of p-MK5 signi cantly decreased in the condition of MAPK4 de ciency. Interestingly, Perander et al reported that the expression of DUSP2 could inhibit ERK3 and ERK4 mediated activation of its downstream substrate MK5 [38]. Therefore, further study on the roles of other couple molecules of MAPK4, which did not be screened in current study, is much valuable for investigation on the exact connections among MAPK4/MK5, AKT and other signaling pathways in the pathology of ALI.…”
Section: Discussionmentioning
confidence: 84%